Morphology of Ranai City Natuna as the small island border city and sustainable development input - Kapiarsa, Asa Bintang; Putra, Bagas Dwipantara; Nabila, Ditasari; Pratama, Ananda; Priyatna, Hendra; Dewi, Delsya Fitri (The Indonesian Journal of Planning and Development, 2024)
The Ranai Urban Area is the center and capital of the Natuna Regency, which is spread throughout the East Bunguran District. As the main service center in Natuna Regency, Ranai will directly affect the shape, structure, and environment of the city, as well as the surrounding rural areas. So that the types of forms and structures of the city can be identified during the process. The purpose of this research is to identify the shape and structure of the city of Ranai as an example of a small town in the area of small islands and the borders of Indonesia that has the potential to become a new growth center and has strategic value for the economy, security, and national defense, meanwhile still considering its sustainability for the future, especially in environmental dimension. The factors used to identify the form and structure of cities in this study are ecological and morphological approaches, which used spatial and descriptive qualitative analysis methods. The results of the study show that the shape of the Ranai Urban Area is a city that is not patterned. Spatial structures are sector models from north to east, and some of them have multicore structures from south to west.Furthermore, Ranai is more suitable for adopting the concept of green urbanism for further development, which aligns with the concept of sustainability.